Biological nitrification inhibitor-trait enhances nitrogen uptake by suppressing nitrifier activity and improves ammonium assimilation in two elite wheat varieties - Adrián Bozal-Leorri; Guntur V. Subbarao; Masahiro Kishii; Leyre Urmeneta; Víctor Kommerell; Hannes Karwat; Hans-Joachim Braun; Pedro Mª Aparicio-Tejo; Iván Ortiz-Monasterio; Carmen González-Murua; Mª Begoña González-Moro (Frontiers in Plant Science, 2022)
Synthetic nitrification inhibitors (SNI) and biological nitrification inhibitors (BNI) are promising tools to limit nitrogen (N) pollution derived from agriculture. Modern wheat cultivars lack sufficient capacity to exude BNIs, but, fortunately, the chromosome region (Lr#n-SA) controlling BNI production in Leymus racemosus, a wild relative of wheat, was introduced into two elite wheat cultivars, ROELFS and MUNAL. Using BNI-isogenic-lines could become a cost-effective, farmer-friendly, and globally scalable technology that incentivizes more sustainable and environmentally friendly agronomic practices. We studied how BNI-trait improves N-uptake, and N-use, both with ammonium and nitrate fertilization, analysing representative indicators of soil nitrification inhibition, and plant metabolism. Synthesizing BNI molecules did not mean a metabolic cost since Control and BNI-isogenic-lines from ROELFS and MUNAL presented similar agronomic performance and plant development. In the soil, ROELFS-BNI and MUNAL-BNI plants decreased ammonia-oxidizing bacteria (AOB) abundance by 60% and 45% respectively, delaying ammonium oxidation without reducing the total abundance of bacteria or archaea. Interestingly, BNI-trait presented a synergistic effect with SNIs since made it also possible to decrease the AOA abundance. ROELFS-BNI and MUNAL-BNI plants showed a reduced leaf nitrate reductase (NR) activity as a consequence of lower soil NO3− formation and a higher amino acid content compared to BNI-trait lacking lines, indicating that the transfer of Lr#-SA was able to induce a higher capacity to assimilate ammonium. Moreover, the impact of the BNI-trait in wheat cultivars was also noticeable for nitrate fertilization, with improved N absorption, and therefore, reducing soil nitrate content.